2019
DOI: 10.2174/1573403x14666180926100811
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study to Evaluate the Effects of Oral N-Acetyl Cysteine on Inflammatory and Oxidative Stress Biomarkers in Rheumatoid Arthritis

Abstract: <P>Background: Rheumatoid Arthritis (RA) is a common inflammatory disease of the joints. Due to the importance of inflammation and oxidative stress in the pathogenesis of RA, drugs that have anti-oxidant and anti-inflammatory properties, such as N-acetyl Cysteine (NAC), can be used as adjunctive therapy in patients with RA. </P><P> Aims: The aim of this study was to evaluate the effects of oral NAC on inflammatory cytokines and oxidative stress in patients with RA. </P><P> Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 37 publications
0
38
0
Order By: Relevance
“…Also, in our previous clinical trial, we found that supplementation with NAC as adjuvant therapy to a standard medication significantly improved pain symptoms in patients suffering from rheumatoid arthritis (RA) 59. Ameliorative effects of NAC on inflammatory and oxidative stress biomarkers may be the mechanism responsible for its beneficial effects on pain symptoms in RA patients 60. In accordance to these studies, the present study also provided further evidence that NAC can be efficacious in improving neuropathic pain associated with diabetic neuropathy, at least in part via ameliorative effects on oxidative stress.…”
Section: Discussionmentioning
confidence: 93%
“…Also, in our previous clinical trial, we found that supplementation with NAC as adjuvant therapy to a standard medication significantly improved pain symptoms in patients suffering from rheumatoid arthritis (RA) 59. Ameliorative effects of NAC on inflammatory and oxidative stress biomarkers may be the mechanism responsible for its beneficial effects on pain symptoms in RA patients 60. In accordance to these studies, the present study also provided further evidence that NAC can be efficacious in improving neuropathic pain associated with diabetic neuropathy, at least in part via ameliorative effects on oxidative stress.…”
Section: Discussionmentioning
confidence: 93%
“…Third, by breaking thiolated proteins and releasing free thiols, NAC can regulate the redox state. 51 Beneficial effects of NAC on oxidative stress biomarkers in various pathological conditions such as pneumonia, 26 rheumatoid arthritis, 27 diabetes mellitus, 52 and myocardial infarction 53 have been reported in previous studies. NAC's influence on oxidative stress biomarkers during brain injury also has been investigated in some experimental studies.…”
Section: Discussionmentioning
confidence: 69%
“…25 Both animal and human studies have further confirmed the favorable influence of NAC treatment on inflammatory and OTS biomarkers. [26][27][28] Due to its ability in modulating oxidative stress and inflammatory conditions, recently therapeutic effects of NAC over a wide range of disorders have been investigated. 24 Previous preclinical studies have demonstrated the potential neuroprotective effects of NAC in treatment of various neurodegenerative diseases such as Huntington's disease, 29 Alzheimer's disease, 30 and Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Reporting. Only 6 RCTs [16,17,26,27,[31][32][33] describe the implementation process of the blind method and were rated as low risk of bias. Four RCTs [18,24,25,44,46] did not describe the implementation process of blinding, and the indicators of this study are biochemical indicators (such as MDA); they are assessed as low risk of bias.…”
Section: Blinding Incomplete Outcome Data and Selectivementioning
confidence: 99%
“…Therefore, research on oxidative stress, SOD antioxidation, and regulation relationship in patients with RA can reveal the pathological mechanism of RA and find new anti-RA drugs. At present, many randomized controlled trials (RCTs) of antioxidants [16][17][18][19][20] in the treatment of RA patients have been published. However, the results and interventions of these RCTs are diverse, and the quality of the evidence provided varies, which cannot provide clinical doctors with evidence to formulate treatment measures against oxidative stress.…”
Section: Introductionmentioning
confidence: 99%